Higher education student´s approaches to learning according to their perception of the context of course and classroom - Javier Goikoetxea Piérola; Iker Ros Martínez de Lahidalga; Karmele Buján Vidales (Universidad de La Rioja, 2014)
The objective of this research was to analyze the relationship between the perception of teaching and learning classroom contexts and perception of course context with approaches to learning for college students. These influences are contrasted by degree, campus and courses. The sample is composed by 524 students of first and second year of Infant and Primary Education, Nursing and Polytechnics of Alava and Guipuzcoa campus. Used scales are the R-SPQ-2F (Biggs, Kember y Leung, 2001) to measure the student´s approaches to learning and the subscales of general Questionnaire of Teaching´s and Learning's Strategies (TS-LSQ) (San Fabián, Argós, Goikoetxea, 2009; Goikoetxea, Aramendi, Bujan, Rekalde y Ros, 2010) to measure the classroom´s context and current context. The study served to confirm the importance of two contextual variables poorly studied until now, the classroom context and the context of course, and its relations with the learning approach of university students. The classroom context is a variable that differentiates between degrees and also is related to significant variations with deep and surface approaches of students. The variable context of course is manifested as a specific variable of degree: the most significant differences for this variable are between the same students when they are in first or second year of career.